Preliminary study on premature infant death of Hainan gibbons (Nomascus hainanus): implications for conservation - Li, Ping; Zhou, Zhaoli; Li, Wenyong; Chen, Yuan; Qi, Xuming (Frontiers in Conservation Science, 2025)
Hainan gibbon (Nomascus hainanus) is China’s only endemic gibbon species and among the world’s rarest primate species. Documenting infant mortality and investigating their underlying causes are essential for informing evidence-based conservation strategies to support population recovery. From 2010 to 2024, we conducted demographic monitoring and behavioral observations of extant gibbon groups in Bawangling area of Hainan Tropical Rainforest National Park, China, recording four infant mortality cases through ad libitum sampling. Among these, three infants (75%) were born to primiparous females, while one (25%) was born to a multiparous female. Notably, we documented for the first time that 4-month-old infants began to move away from their mothers, and infant mortality events coincided temporally with their initial attempts at independent activities. These findings suggest that inadequate parenting experience (primiparity) in females and premature infant independence would be critical determinants of neonatal survival in Hainan gibbons. Specifically, infants born to primiparous mothers, particularly those aged 4-6 months, face elevated risks of accidental mortality. We propose that conservation efforts prioritize enhanced patrols and rescue protocols during this high-vulnerability stage. Long-term monitoring of infant birth-death dynamics, coupled with rigorous investigation of causative factors, is imperative for the conservation and population recovery of this Critically Endangered species.